2014
DOI: 10.1111/ene.12466
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in relatives of patients with myotonic dystrophy: a population‐based cohort study

Abstract: The present study does not support an increased risk of cancer in non-DM relatives of DM patients suggesting that cancer and DM are associated through derived effects of the DM genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, the association in our study was seen only in parents and was not in siblings or offspring. A previous large population-based study of cancer risk in family members of DM1 patients suggested that cancer risk in DM families (disease subtype was not available) was driven by individuals’ DM status [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the association in our study was seen only in parents and was not in siblings or offspring. A previous large population-based study of cancer risk in family members of DM1 patients suggested that cancer risk in DM families (disease subtype was not available) was driven by individuals’ DM status [31].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory neuropathies have likewise been amenable to treatment but still recognised to cause significant morbidity [184][185][186][187][188][189][190]. Myotonic dystrophy is a channelopathy with CNS as well as myopathic involvement and in common with other disorders of this class has overlap with neurodegenerative diseases [191][192][193][194]. The inflammatory neuropathies in some cases form an overlap with CNS infections [195][196][197][198][199][200][201].…”
mentioning
confidence: 99%